2012
DOI: 10.1186/2110-5820-2-31
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitic emergencies in the intensive care unit: a special focus on cryoglobulinemic vasculitis

Abstract: Vasculitis is characterized by the infiltration of vessel walls by inflammatory leukocytes with reactive damage and subsequent loss of vessel integrity. The clinical course of systemic vasculitis may be punctuated by acute life-threatening manifestations that require intensive care unit (ICU) admission. Furthermore, the diagnosis may be established in the ICU after admission for a severe inaugural symptom, mostly acute respiratory failure. Among the systemic vasculitides, cryoglobulinemic vasculitis (CV) has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…However, none of the patients yielded MCS implies that HCV RNA might be crucial in the pathogenesis of MC‐associated vasculitis and eradication of HCV infection is indeed the effective treatment for most MCS patients . In addition, all the differences including gender bias, cirrhosis rate, and IgG, IgM, FIB‐4 and C4 levels observed between the MC (+) and MC (−) patients have been consistently reported in the CHC studies . It did not only strengthen the reliability of our results, but also indicate the core manifestations of HCV‐associated MC, regardless of the presence of the virus.…”
Section: Discussionsupporting
confidence: 82%
“…However, none of the patients yielded MCS implies that HCV RNA might be crucial in the pathogenesis of MC‐associated vasculitis and eradication of HCV infection is indeed the effective treatment for most MCS patients . In addition, all the differences including gender bias, cirrhosis rate, and IgG, IgM, FIB‐4 and C4 levels observed between the MC (+) and MC (−) patients have been consistently reported in the CHC studies . It did not only strengthen the reliability of our results, but also indicate the core manifestations of HCV‐associated MC, regardless of the presence of the virus.…”
Section: Discussionsupporting
confidence: 82%
“…Cryo-GN appears in more than 20% of cases and it usually presents itself with mild proteinuria, microscopic hematuria and hypertension. In 70%-80% of those cases renal biopsy reveals type 1 membranoproliferative GN [11]. Our patient was uncooperative for kidney biopsy and therefore Cryo-GN was diagnosed in accordance with the previously defined clinical criteria [12,13].…”
Section: Discussionsupporting
confidence: 54%
“…Retamozo et al reviewed a total of 279 cases with life-threatening CryoVas (30 from their department) and found that in 232 patients (83%) it was the first manifestation of cryoglobilinemia [10]. They suggested awareness of life-threatening CryoVasas a differential diagnosis in ICU [11].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, renal involvement is the most common cryoglobulinaemic vasculitis related visceral manifestation with AKI seen in more than 30% of cases. Presenting as a multisystem disorder is not uncommon and although ICU experience is scant results from one centre suggest early ICU referral may translate into an excellent initial outcome [29].…”
Section: Pulmonary Renal Syndrome Associated With Thrombotic Microangmentioning
confidence: 98%